# Standard Equation of an Hyperbola

We will learn how to find the standard equation of a hyperbola.

Let S be the focus, e (> 1) be the eccentricity and line KZ its directrix of the hyperbola whose equation is required.

From the point S draw SK perpendicular to the directrix KZ. The line segment SK and the produced SK divides internally at A and externally at A’ respectively in the ratio e : 1.

Then,

$$\frac{SA}{AK}$$ = e : 1

⇒ SA = e  ∙ AK …………. (ii)

and  $$\frac{SA'}{A'K}$$ =  e : 1

⇒ SA' = e  ∙ A'K …………………. (ii)

The points A and A' he on the required hyperbola because according to the definition of hyperbola A and A’are such points that their distance from the focus bear constant ratio e (>1) to their respective distance from the directrix, therefore A and A' he on the required hyperbola.

Let AA’ = 2a and C be the mid-point of the line segment AA'. Therefore, CA = CA' = a.

Now draw CY perpendicular to AA’ and mark the origin at C. CX and CY are assumed as x and y-axes respectively.

Now, adding the above two equations (i) and (ii) we have,

SA + SA' = e (AK + A'K)

⇒ CS - CA + CS + CA' =  e (AC - CK + A’C + CK)

⇒ CS - CA + CS + CA' =  e (AC - CK + A’C + CK)

Now put the value of CA = CA' = a.

⇒ CS - a + CS + a = e (a - CK + a + CK)

⇒2CS = e (2a)

⇒ 2CS = 2ae

⇒ CS = ae …………………… (iii)

Now, again subtracting above two equations (i) from (ii) we have,

⇒ SA' - SA = e (A'K - AK)

⇒ AA'= e {(CA’ + CK) - (CA - CK)}

⇒ AA' = e (CA’ + CK - CA + CK)

Now put the value of CA = CA' = a.

⇒ AA' = e (a + CK - a + CK)

⇒ 2a = e (2CK)

⇒ 2a = 2e (CK)

⇒ a = e (CK)

⇒ CK = $$\frac{a}{e}$$ ………………. (iv)

Let P (x, y) be any point on the required hyperbola and from P draw PM and PN perpendicular to KZ and KX respectively. Now join SP.

According to the graph, CN = x and PN = y.

Now form the definition of hyperbola we get,

SP = e PM

⇒ Sp$$^{2}$$= e$$^{2}$$PM$$^{2}$$

⇒ SP$$^{2}$$ = e$$^{2}$$KN$$^{2}$$

⇒ SP$$^{2}$$ = e$$^{2}$$(CN - CK)$$^{2}$$

⇒ (x - ae)$$^{2}$$ + y$$^{2}$$ = e$$^{2}$$(x - $$\frac{a}{e}$$)$$^{2}$$, [From (iii) and (iv)]

⇒ x$$^{2}$$ - 2aex + (ae)$$^{2}$$ + y$$^{2}$$ = (ex - a)$$^{2}$$

⇒ (ex)$$^{2}$$ - 2aex + a$$^{2}$$ = x$$^{2}$$ - 2aex + (ae)$$^{2}$$ + y$$^{2}$$

⇒ (ex)$$^{2}$$  - x$$^{2}$$ - y$$^{2}$$ = (ae)$$^{2}$$ - a$$^{2}$$

⇒ x$$^{2}$$(e$$^{2}$$ - 1) - y$$^{2}$$ = a$$^{2}$$(e$$^{2}$$ - 1)

⇒ $$\frac{x^{2}}{a^{2}}$$ - $$\frac{y^{2}}{a^{2}(e^{2} - 1)}$$ = 1

We know that a$$^{2}$$(e$$^{2}$$ - 1) = b$$^{2}$$

Therefore, $$\frac{x^{2}}{a^{2}}$$ - $$\frac{y^{2}}{b^{2}}$$ = 1

For all the points P (x, y) the relation $$\frac{x^{2}}{a^{2}}$$ - $$\frac{y^{2}}{b^{2}}$$ = 1 satisfies on the required hyperbola.

Therefore, the equation $$\frac{x^{2}}{a^{2}}$$ - $$\frac{y^{2}}{b^{2}}$$ = 1 represents the equation of the hyperbola.

The equation of a hyperbola in the form of $$\frac{x^{2}}{a^{2}}$$ - $$\frac{y^{2}}{b^{2}}$$ = 1 is known as the standard equation of the hyperbola.

The Hyperbola